Portfolio construction with particle swarm optimization in Turkish stock market - Salman, Özgür (İstanbul Bilgi Üniversitesi, 2018)
[Abstract Not Available]
Parçacık sürüoptimizasyonu ile Türkiye pay piyasasında portfolyo üretimi